(untitled) (Texas Journal of Medical Science, 2024)
Laparoscopic cholecystectomy (LC) is a surgical procedure frequently performed in benign gallbladder diseases since its description and has become the gold standard surpassing open cholecystectomy due to its numerous advantages. Like any new technique, adaptation problems were experienced in the early days of its application and complication rates were relatively high. In subsequent years, the evolution of minimally invasive surgery and the growing experience of surgeons have facilitated the application of LC and led to various modifications. This article aims to explore the evolution of cholecystectomy techniques, focusing on standard LC and over 50 modified techniques documented in the medical literature